2022
DOI: 10.3389/fimmu.2022.823160
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Cryoglobulinemia in Direct-Acting Antiviral-Treated Asian Hepatitis C Patients With Sustained Virological Responses: A 4-Year Prospective Cohort Study

Abstract: BackgroundHow cryoglobulinemia evolves after sustained virological response (SVR) following direct-acting antiviral (DAA) treatment in Asian hepatitis C virus (HCV)-infected patients remains elusive.MethodsA prospective cohort study was conducted in 422 Taiwanese patients (358 completed DAA therapy and 353 experienced SVRs). Serum cryoglobulins were surveyed at baseline and every 3-6 months posttherapy.ResultsOf 422, 227 (53.8%) had cryoglobulinemia, 8 (1.89%) had cryoglobulinemic vasculitis. Of 227, 54 (23.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Cryocrit and RF show a significant decrease and C4 levels increase after therapy [40 ▪ ], with persistent cryoglobulinemia associated with advanced liver fibrosis [41,42]. Cryoglobulins reduction has persisted over a 4-years follow-up period in an Asian cohort [43]. Clinical worsening and relapse are associated with high rheumatoid factor levels before treatment [40 ▪ ,44].…”
Section: Therapy and Prognosismentioning
confidence: 99%
“…Cryocrit and RF show a significant decrease and C4 levels increase after therapy [40 ▪ ], with persistent cryoglobulinemia associated with advanced liver fibrosis [41,42]. Cryoglobulins reduction has persisted over a 4-years follow-up period in an Asian cohort [43]. Clinical worsening and relapse are associated with high rheumatoid factor levels before treatment [40 ▪ ,44].…”
Section: Therapy and Prognosismentioning
confidence: 99%
“…In this regard, it has been shown that the immune response triggered by chronic HCV infection leads to the formation of cryoglobulins, causing vasculitis and various clinical manifestations such as skin lesions, joint pain, and kidney involvement [ 3 ]. Before the advent of direct-acting antivirals (DAAs), HCV infection was a common cause of MC [ 7 ]. However, with the introduction of DAAs for the treatment of HCV, the landscape of mixed cryoglobulinemia has seen an etiological shift toward autoimmune and lymphoproliferative disorders, HCV-related MC treated with DAA has shown dramatic amelioration and prevented further organ damage [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Before the advent of direct-acting antivirals (DAAs), HCV infection was a common cause of MC [ 7 ]. However, with the introduction of DAAs for the treatment of HCV, the landscape of mixed cryoglobulinemia has seen an etiological shift toward autoimmune and lymphoproliferative disorders, HCV-related MC treated with DAA has shown dramatic amelioration and prevented further organ damage [ 7 ]. In this article, we summarize the clinical course and diagnostic approach of a case of MC type III secondary to HCV infection.…”
Section: Introductionmentioning
confidence: 99%